Macroscopic and mesoscopic properties of HTPB propellant under low temperature dynamic biaxial compression loading. (February 2023) - Geng, Tingjing; Qiang, Hongfu; Wang, Zhejun; Wang, Xueren; Zhu, Zhaojun; Qiao, Dong
Abstract: In order to study the macroscopic mechanical properties and meso damage mechanism of solid fuel hydroxy-terminated polybutadiene (HTPB) propellant under low temperature and dynamic biaxial compression loading, the INSTRON high strain rate hydraulic testing machine was used to carry out dynamic biaxial compression test of HTPB propellant in the temperature range of −50 °C ∼ -30 °C and the strain rate range of 1s −1 –85s −1 . Meanwhile, the control test at room temperature (25 °C) was set up, and microcomputed tomography (Micro-CT) was used to observe and quantitatively characterize the meso damage of the loaded specimens. The test results show that temperature and strain rate significantly affect the mechanical properties of HTPB propellant in biaxial compression, and the mechanical properties under biaxial compression loading are more susceptible to temperature than strain rate. In addition, there is a significant difference between uniaxial and biaxial strength under compression loading, and finally, the effect of temperature and strain rate on mechanical properties is closely related to the variation in properties and mesoscopic damage mechanisms of HTPB propellants. This paper can deepen researchers' understanding of the performance of composite solid propellant and other energetic materials at the macro and micro level, and provide more effective theoretical and technical support for accurate analysis of the grain structure integrity of airborne missile solid rocket motor (SRM) under low temperature ignition conditions. Highlights: Realize the research on mechanism of HTPB propellant under low temperature and dynamic biaxial compression firstly. The reliability of the indirect low temperature method is verified by theoretical calculations and experimental tests. The difference of uniaxial and biaxial compressive strength of HTPB propellant is analyzed firstly. Quantitative characterisation of HTPB propellant damage in fine detail under dynamic biaxial compression loading.